Hepaticojejunostomy as a Palliative Procedure in Biliary Obstruction due to Pancreatic Tumors.: about 39 cases - Estefan, Alberto; Pomi, Jorge; Baldizán, Jorge; Pignata, Daniel; Praderi, r (Cirugía del Uruguay, 1981)
The authors analyze retrospectively 39 hepaticojejunostomies used in the treatment of non resectable cephalic cancer of the pancreas.